1989
DOI: 10.1007/bf00277262
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and manifest diabetes mellitus in young patients with friedreich's ataxia: no evidence of immune process behind the islet cell destruction

Abstract: Friedreich's ataxia is known to be associated with diabetes mellitus in up to 20% of the patients. However, type, development and course of diabetes mellitus are not well characterised. We report on 3 patients (2 female and 1 male, age 13-20 years) with the combination of Friedreich's ataxia and diabetes mellitus. Diabetes mellitus was characterised as follows: (1) it was strictly insulin-dependent and ketosis-prone, (2) the average insulin requirement was 1 U/kg body weight, (3) the HLA haplotype was not typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…Diabetes in FRDA has been attributed to insulin deficiency, 21,22 but more recently emphasis was placed on the role of insulin resistance, with some studies reporting normal insulin secretion. 19,2328,47 The present study confirms that FRDA patients, although young and having a rather low BMI, have increased body fat and are insulin resistant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes in FRDA has been attributed to insulin deficiency, 21,22 but more recently emphasis was placed on the role of insulin resistance, with some studies reporting normal insulin secretion. 19,2328,47 The present study confirms that FRDA patients, although young and having a rather low BMI, have increased body fat and are insulin resistant.…”
Section: Discussionmentioning
confidence: 99%
“…21 One causal factor for FRDA diabetes was proposed to be nonautoimmune β -cell loss. 22 Other studies reported no difference in insulin output, 23 and demonstrated insulin resistance at the whole body and cellular level. 19,2426 Using 31 P magnetic resonance spectroscopy, impaired muscular mitochondrial function was demonstrated in vivo in FRDA patients, 27,28 similar to findings in insulin-resistant offspring of T2D patients.…”
mentioning
confidence: 98%
“…FRDA patients are insulin resistant before being diabetic (9), and higher incidence of glucose intolerance and insulin resistance has been reported in family members of FRDA patients (42,43). However, other reports suggest a primary beta-cell involvement in FRDA (44), and a pathogenic mechanism primarily involving beta-cell failure has been proposed based on studies in other mitochondrial disorders (45,46) and on the pancreatic conditional frataxin knock-out (6). Here, we confirm that insulin resistance is present in all tested non-diabetic FRDA patients, strongly supporting the hypothesis suggested by our gene expression data that insulin target tissues are relevant in the pathogenesis of diabetes in FRDA.…”
Section: Discussionmentioning
confidence: 99%
“…Однако в литературе описаны случаи инсулинозависимого СД при АФ, обусловленного потерей ост-ровковых клеток, но без HLA-ассоциации и аутоиммунной де-струкции β-клеток. Связь между геном атаксии Фридрейха и геном, определяющим предрасположенность к СД, не вы-явлена [16].…”
Section: /2010unclassified